2004
DOI: 10.1080/01926230490261348
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Exposure to Arsenic Through Drinking Water Alters Expression of Cancer-Related Genes in Rat Liver

Abstract: Although arsenic exposure causes liver disease and/or hepatoma, little is known about molecular mechanisms of arsenic-induced liver toxicity or carcinogenesis. We investigated the effects of arsenic on expression of cancer-related genes in a rat liver following subchronic exposure to sodium arsenate (1, 10, 100 ppm in drinking water), by using real-time quantitative RT-PCR and immunohistochemical analyses. Arsenic accumulated in the rat liver dose-dependently and caused hepatic histopathological changes, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Thus, the loss of this protective factor could help explain the induction of ODD seen in this study. Moreover, this MMA III -induced depletion of PTEN expression is consistent with that seen during malignant transformation and tumor formation by other arsenicals (Cui et al 2004; Tokar et al, 2010a; Sun et al 2012), suggesting a common mechanism in several models of arsenical-induced carcinogenesis. Previous studies have shown that arsenicals (iAs, MMA III ) can alter signaling via Akt phosphorylation but these exposures had no effect on PTEN levels (Paul et al 2007).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, the loss of this protective factor could help explain the induction of ODD seen in this study. Moreover, this MMA III -induced depletion of PTEN expression is consistent with that seen during malignant transformation and tumor formation by other arsenicals (Cui et al 2004; Tokar et al, 2010a; Sun et al 2012), suggesting a common mechanism in several models of arsenical-induced carcinogenesis. Previous studies have shown that arsenicals (iAs, MMA III ) can alter signaling via Akt phosphorylation but these exposures had no effect on PTEN levels (Paul et al 2007).…”
Section: Discussionsupporting
confidence: 80%
“…For instance, phosphatase and tensin homologue (PTEN) is a tumor suppressor gene that is commonly mutated or deleted in cancers, but plays vital roles in proper DNA repair and DNA damage response pathways (Ming and He, 2012). Chronic exposure to arsenic depletes the expression of PTEN during cancer formation in vivo and during malignant transformation in vitro (Cui et al 2004; Tokar et al, 2010a; Sun et al 2012). Thus, not only can exposure to arsenicals induce ROS-mediated ODD (Nesnow et al, 2002; Gomez et al, 2006; Kojima et al, 2009; Wnek et al, 2011), it can also inactivate various factors involved in DNA repair, thereby perturbing the repair process (Cui et al 2004; Tokar et al, 2010a; Wnek et al, 2011; Sun et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin D1 overexpression is important for HCC formation and is considered a hepatic oncogene (Deane et al 2001). Overexpression of cyclin D1 has been reported in arsenic-transformed cells (Chen et al 2001b), during arsenic-induced skin co-carcinogenicity in mice (Rossman et al 2001), in dimethylarsinic acid–induced bladder proliferative lesions in rats (Wei et al 2002), in chronic arsenate-exposed rats (Cui et al 2004), and in the livers of mice bearing HCC induced by in utero exposure to arsenic (Liu et al 2004). Cyclin D1 overexpression, together with other positive cell cycle regulators such as cyclin E, cdk4, cdkn2a, cdkn2b, and PCNA was evident in arsenic-exposed tissues in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For an example, Park and his colleagues report that p27 Kip1 expression is not altered in arsenic trioxide-induced cell cycle arrest and apoptosis in myeloma cells [8]. While another study demonstrates that p27 Kip1 mRNA level is increased after a 4-month arsenic exposure [9]. Recently, arsenic trioxide is also reported to induce p27 Kip1 expression in breast cancer cell line and hepatocellular carcinoma (HCC) cells [10,11].…”
Section: Introductionmentioning
confidence: 99%